Cephalometric evaluation of preoperative incisor inclination in patients with class ii dentofacial deformities treated with mandibular advancement - Gonçalves, Gabriela Mayrink; Moreira, Roger William Fernandes; Marotta Araujo, Marcelo (Brazilian Dental Science, 2015)
ABSTRACT Objective: To evaluate cephalometrically the preoperative incisor inclination of 30 patients with Class II malocclusion, who were treated with mandibular advancement. Materials and Methods: Thirty immediate preoperative lateral cephalograms were photographed to be used in Dolphin Imaging Software. Linear and angular measurements were traced and analyzed. Each tracing was repeated twice with 1-week interval by the same operator. The measures were tabulated at Microsoft Excel and submitted to Student’s-t test and mean measures were compared with the normal values. The intraclass correlator coefficient was used to test the intraexaminer reliability. Results: The intraclass correlation coefficient was >0.9 and it featured a high reliability. Mean values of lower incisors differed from normal values, presenting labial inclination compared to normal values. Conclusion: In this study, the results showed that Class II patients that will be submitted a mandibular advancement (orthognathic surgery) had dental compensations and the lower incisors are more proclined comparing to the standard values. Keywords: Orthognathic surgery; Orthodontics; Cephalometry.